2016
DOI: 10.5966/sctm.2015-0247
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the cAMP and Transforming Growth Factor-β Pathway Increases Proliferation to Promote Re-Epithelialization of Human Stem Cell-Derived Retinal Pigment Epithelium

Abstract: Retinal pigment epithelium (RPE) cell integrity is critical to the maintenance of retinal function. Many retinopathies such as age-related macular degeneration (AMD) are caused by the degeneration or malfunction of the RPE cell layer. Replacement of diseased RPE with healthy, stem cell-derived RPE is a potential therapeutic strategy for treating AMD. Human embryonic stem cells (hESCs) differentiated into RPE progeny have the potential to provide an unlimited supply of cells for transplantation, but challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…SNAI1 also mediated the increase of fibronectin and α-smooth muscle actin expression, and, consequently, the migratory activity of RPE cells [ 88 ]. As further confirmation of this, it was reported that TGF-β1 led to an increase in expression of mesenchymal markers in stem cell-derived RPE cells, along with a decrease in expression of epithelial markers [ 89 ], and TGF-β2 promoted ARPE-19 cell invasion into collagen by mediating the expression urokinase-type plasminogen activator, a serine protease involved in tissue remodeling and cell migration [ 90 ]. Nevertheless, TGF-β2 was unable to initiate EMT in primary porcine RPE isolated as sheets, cultured in vitro on lens capsules, and as such, maintaining cell–cell contact [ 91 ].…”
Section: Tgf-β Signaling In Rpementioning
confidence: 73%
“…SNAI1 also mediated the increase of fibronectin and α-smooth muscle actin expression, and, consequently, the migratory activity of RPE cells [ 88 ]. As further confirmation of this, it was reported that TGF-β1 led to an increase in expression of mesenchymal markers in stem cell-derived RPE cells, along with a decrease in expression of epithelial markers [ 89 ], and TGF-β2 promoted ARPE-19 cell invasion into collagen by mediating the expression urokinase-type plasminogen activator, a serine protease involved in tissue remodeling and cell migration [ 90 ]. Nevertheless, TGF-β2 was unable to initiate EMT in primary porcine RPE isolated as sheets, cultured in vitro on lens capsules, and as such, maintaining cell–cell contact [ 91 ].…”
Section: Tgf-β Signaling In Rpementioning
confidence: 73%
“…Like high-phagocytic RPE cells, low-phagocytic RPE cells lacked the mesenchymal marker protein αSMA and retained localization of the tight junction associated protein ZO-1 at cell-cell contacts. These results suggest that low-phagocytic RPE cells redifferentiated into an epithelial phenotype during the post-proliferative phase in culture ( Choudhary et al., 2016 ). Furthermore, they imply that scoring F-actin organization as described provides information of RPE-like characteristics beyond testing epithelialization.…”
Section: Discussionmentioning
confidence: 87%
“…Of these, the neuroactive ligand-receptor interaction signaling pathway has been reported to be associated with the progression of renal cell carcinoma in bioinformatics studies [50]. In addition, previous studies have suggested that cAMP-related signaling could control apoptosis induction and cell growth [51, 52], while another study demonstrated that cAMP was an inhibitor of cell cycle progression and apoptosis in gastric cancer cells [53]. Zhang et al [54] showed that the ECM–receptor interaction pathway played a significant role in tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%